2001
DOI: 10.1111/j.8755-8920.2001.460204.x
|View full text |Cite
|
Sign up to set email alerts
|

Choriocarcinoma Cells Modulate the Cytokine Production of Decidual Large Granular Lymphocytes in Coculture

Abstract: MHC class I positive/negative CC modulate the cytokine production of decidual LGL in different ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
2
11
1
1
Order By: Relevance
“…Uterine NK cells are a rich source of many different cytokines and growth factors including TNF-α, IL-10, GM-CSF, IL-1β, TGF-β1, CSF-1, LIF and IFN-γ (Saito et al, 1993;Jokhi et al, 1994;Jokhi et al, 1997;Rieger et al, 2001). In general investigation of cytokine production has been on uNK cells purified from early pregnancy decidua, with no separation of decidua basalis and decidua parietalis, although Von Rango et al (2003) compared cytokine production by uNK cells from decidua basalis and decidua parietalis and noted differences in cytokine profile.…”
Section: Functional Investigationsmentioning
confidence: 99%
“…Uterine NK cells are a rich source of many different cytokines and growth factors including TNF-α, IL-10, GM-CSF, IL-1β, TGF-β1, CSF-1, LIF and IFN-γ (Saito et al, 1993;Jokhi et al, 1994;Jokhi et al, 1997;Rieger et al, 2001). In general investigation of cytokine production has been on uNK cells purified from early pregnancy decidua, with no separation of decidua basalis and decidua parietalis, although Von Rango et al (2003) compared cytokine production by uNK cells from decidua basalis and decidua parietalis and noted differences in cytokine profile.…”
Section: Functional Investigationsmentioning
confidence: 99%
“…Cytokine secretion of TNF-α, TGF-β1, IFN-γ, IL-8 and IL6 by uNK cells significantly increased in the present study following ULBP1 binding. Human uNK cells produce a variety of cytokines and growth factors, including TNF-α, IL-10, granulocyte-macrophage colony-stimulating factor, IL-1, TGF-β1, colony-stimulating factor-1, leukemia inhibitory factor, IFN-γ (45–47), IL-6 (9), IL-8 and interferon-inducible protein-10 (8), and the roles that these cytokines and growth factors have in EVT invasion has been investigated in previous studies. A study by Bauer et al (26) demonstrated that TNF-α inhibits trophoblast invasion through the elevation of plasminogen activator inhibitor-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, their levels diminish drastically toward the end of gestation (Williams et al 2009;Bulmer et al 2010). uNK are a rich source of a range of cytokines and angiogenic growth factors (Jokhi et al 1994(Jokhi et al , 1997Li et al 2001;Rieger et al 2001;Hanna et al 2006;Lash et al 2006aLash et al , 2010a.…”
Section: Immune Tolerancementioning
confidence: 99%